Comparative study between patients with acute appendicitis treated in primary care units and in emergency hospitals - Bon,Thiago de Paula (2014)
Objective: To retrospectively analyze the relationship of time of care, combined with possible post-appendectomy complications, with the promptness of transfer of patients seen in Emergency Care Units (UPA) to the emergency hospital.Methods: We analyzed patients with preoperative diagnosis of acute appendicitis undergoing appendectomy from January to July 2012. Patients were divided into two groups according to the site of the first care. Group A included patients who received initial care directly in the emergency department of the Lourenço Jorge County Hospital (HMLJ) and group B consisted of patients seen in the UPA and forwarded to HMLJ to undergo surgical treatment.Results: the average time between initial treatment and surgery in group A was 29 hours (SD = 21.95) and 54 hours in group B (SD = 54.5). Considering the onset of symptoms, the patients in group A were operated on average 67 hours after (SD = 42.55), while group B, 90 hours (SD = 59.58). After the operation, patients in group A were hospitalized, on average, for 94 hours (SD = 73.53) and group B, 129 hours (SD = 193.42).Conclusion: there was no significant difference in the time elapsed between the onset of symptoms, initial treatment and early surgical treatment, or time elapsed between surgery and discharge.